Interpretation of the Tribeč Mts. deep geological structure based on results of geophysical, mainly magnetotelluric modelling - BEZÁK, Vladimír; VOZÁR, Ján; HVOŽDARA, Milan (Contributions to Geophysics and Geodesy, 2011)
Magnetotelluric measurements (MT) in the southeast (SE) part of MT–15 profile in the frame of CELEBRATION 2000 project identified a subhorizontal zone with higher conductivity in the depth of cca 2–6 km below the Tribeč Mts. surface. This zone is interpreted as a complex of metamorphic rocks under the tectonically overlaying granites. The original presuppositions collected through other geophysical methods on the existence of such a complex are thereby confirmed. Apart from this finding, the MT measurements identified other conductive zones in the Tribeč mountain range and its surroundings. Those are close to the surface and belong to sedimentary rocks and volcanites. The steep, narrow and deeply penetrating conductive zone at the north-western edge of Tribeč Mts. can be interpreted as a deep Neogene shear zone. Subhorizontal conductive zone in SE part of the cross-section under the volcanic complexes is interpreted as the older mylonitized zone. This zone may be saturated by fluids, and is possibly of carbon origin and mineralized, connected with volcanic activity.